Associations of quality of life with health-related characteristics among children with autism. (October 2018) - Kuhlthau, Karen A; McDonnell, Erin; Coury, Dan L; Payakachat, Nalin; Macklin, Eric
We examine whether behavioral, mental health, and physical health characteristics of children with autism are associated with baseline and change in health-related quality of life. We measured health-related quality of life with the Pediatric Quality of Life Inventory 4.0 total scores from children enrolled in the Autism Treatment Network. We used linear mixed model regressions with random slopes. Predictors of lower health-related quality of life at baseline included demographic and insurance characteristics, diagnosis, higher Child Behavior Checklist internalizing and externalizing scores, sleep problems by Children's Sleep Habits Questionnaire, seizures, gastrointestinal problems, and mental health problems. Several characteristics had different associations over time. This study demonstrates that in addition to behavioral and autism-related characteristics, physical and mental health conditions are associated with health-related quality of life in children with autism.